On the Category of Methodological Status of Science - Walczak, Monika (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The aim of my paper is to consolidate and clarify the meaning of the term methodological status of science and thus increase the methodological self-consciousness of scientists, methodologists and philosophers of science. The present considerations serve the purpose of self-reflection, because the categories in question apply also to the methodology and philosophy of science. The notion of methodological status is the most general category by means of which it is possible to characterize science in general, and particular scientific disciplines in a formal terms. Although used by many authors, when drawing attention to the determinants of the status of science (the object of research, research objective, research problems, research method, structure of knowledge, scientific language, genesis and history of science), it has not been defined precisely yet, as regards specification of its meaning and the meaning of the determinants that constitute it. In my text I would like to fill in the gap.